2011
DOI: 10.1186/1749-7922-6-35
|View full text |Cite
|
Sign up to set email alerts
|

A technical modification for percutaneous tracheostomy: prospective case series study on one hundred patients

Abstract: The purpose of this study is to describe a technical modification of percutaneous tracheostomy that combines principles of the Percu Twist™ and the Griggs-Portex® methods in a reusable kit. One hundred patients underwent the procedure. There were no false passage, tube misplacement, or deaths related to the procedure. There were two minor bleedings managed conservatively. The technical modification described in this study is safe and simple to execute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…The median procedure length was shorter in the US group, with the length of bronchoscopy-guided PDT being similar to that of previous [14][15][16][17][18][19][20][21][22][23] 13 [10][11][12][13][14][15][16][17][18][19][20][21][22] .004…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The median procedure length was shorter in the US group, with the length of bronchoscopy-guided PDT being similar to that of previous [14][15][16][17][18][19][20][21][22][23] 13 [10][11][12][13][14][15][16][17][18][19][20][21][22] .004…”
Section: Discussionsupporting
confidence: 82%
“…The median procedure length was shorter in the US group than in the bronchoscopy group (12 [8][9][10][11][12][13][14][15] minutes vs 15 [15-21.5] minutes, P = .028). The puncture site was changed after the US in 9 (18.4%) patients.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…The airway cast was produced using a negative-pressure chamber that facilitated passive passage of silicone into the airways and avoided airway distension (26). Current use of airway ultrasound is limited to a few indications, such as percutaneous tracheostomy (27) and confirmation of endotracheal position during intubation (28). Our findings extend previous use of tracheal ultrasound in lambs to suggest a role for tracheal ultrasound in the evaluation of tracheomalacia in human newborns (29).…”
Section: Discussionsupporting
confidence: 76%
“…Sustić and colleagues (23) used Doppler US and Rezende-Neto et al (24) used US to ensure that the withdraw level of the endotracheal tube would prevent cuff perforation by the seeking needle. In our study, US examination in the midline-sagittal plane during the pullback of the cuff showed the tube shafts as echogenic "doubleline" structures near the tracheal anterior air interface that ended with the irregular round opacities of the cuff balloon.…”
Section: Discussionmentioning
confidence: 99%